2016
DOI: 10.1038/srep31758
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cellular senescence-specific genes by comparative transcriptomics

Abstract: Cellular senescence is defined as permanent cell cycle arrest induced by various stresses. Although the p53 transcriptional activity is essential for senescence induction, the downstream genes that are crucial for senescence remain unsolved. Here, by using a developed experimental system in which cellular senescence or apoptosis is induced preferentially by altering concentration of etoposide, a DNA-damaging drug, we compared gene expression profiles of senescent and apoptotic cells by microarray analysis. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 44 publications
(58 reference statements)
10
70
0
Order By: Relevance
“…Since PRODH is known to produce ROS as a byproduct of proline oxidation (Donald et al, 2001), and ROS induce senescence through oxidative damage (Campisi, 2013;Salama et al, 2014;Lu and Finkel, 2008), we first examined whether overexpression of PRODH results in ROS accumulation. In accordance with our previous results (Nagano et al, 2016), ectopic expression of PRODH modestly induced senescence in U2OS cells, as judged using SA-β-Gal and EdU assays ( Fig. 3A-C).…”
Section: Prodh Induces Senescence Via Ros Productionsupporting
confidence: 93%
See 4 more Smart Citations
“…Since PRODH is known to produce ROS as a byproduct of proline oxidation (Donald et al, 2001), and ROS induce senescence through oxidative damage (Campisi, 2013;Salama et al, 2014;Lu and Finkel, 2008), we first examined whether overexpression of PRODH results in ROS accumulation. In accordance with our previous results (Nagano et al, 2016), ectopic expression of PRODH modestly induced senescence in U2OS cells, as judged using SA-β-Gal and EdU assays ( Fig. 3A-C).…”
Section: Prodh Induces Senescence Via Ros Productionsupporting
confidence: 93%
“…Consistent with this, we showed that PRODH overexpression induces DNA damage. Since we have previously revealed that PRODH is upregulated by p53 during senescence (Nagano et al, 2016), these results indicate that PRODH upregulated by p53 in response to senescence-inducing stresses amplifies DNA damage through ROS generation, thereby inducing senescence.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations